PEMANFAATAN TEORI IMAGE RESTORATION DALAM PENELITIAN KUALITATIF DAN KUANTITATIF DI ERA TEKNOLOGI DIGITAL - Ratna Komala (Jurnal Ranah Komunikasi, 2022)
This paper aims to map the use of the Image Restoration Discourse theory or approach to analyze crises both in organizations and individuals. Digital technology has a significant influence on the study of crisis communication, where internet-based communication platforms, such as social media, allow information to be widely disseminated, in real time interaction. On the one hand, digital technology is a solution to the crisis, but on the other hand it is a source of crisis. Using the literature review method, various previous research related to the theory, also known as Image Repair Theory, were collected, both classical and contemporary. In conclusion, Image Repair theory is relevant to be used as an analytical tool for various research units, including its relation to the use of digital technology.